Benefits of Equine-Assisted Therapy on the Gait Variables in People Older Than 18 Years With Motor Impairments Secondary to Stroke or Multiple Sclerosis - Anguita Córdova, Karina Daniela (2019)
We analyzed the results obtained from the benefits of equine-assisted therapy in gait variables (balance, coordination and postural control) on people over eighteen years old with transitory or permanent physical and/or physiological deficiencies secondary to stroke (ischemic or hemorrhagic) or multiple sclerosis (relapse remission and/or secondary progressive) after their participation in the therapy. The methodology used was a narrative review of the existing up-to-date literature with a systematic research method on the following databases: PubMed, SciELO, LILACS, and Scopus in order to make a bibliographical update about the topic. At last, eleven articles were selected for further analysis (systematic reviews, Randomized Clinical Trial, a case-control study). The results of these articles agree that the use of equine-assisted therapy can be effective in improving the variables mentioned above. However, there is not enough information available on different search engines, so there is a need to conduct studies with a representative sample size where they have to use the same evaluation scales in order to be able to objectify and standardize the results. Conclusion: nowadays around the world there are different studies, which indicate that equine-assisted therapy can be an effective tool in the rehabilitation of the different components that affect gait, such as balance or coordination, in people with motor impairments secondary to stroke (ischemic or hemorrhagic) or Multiple Sclerosis (relapse remission and/or secondary progressive). Therefore, we could consider the use of equine-assisted therapy as a therapeutic tool in the rehabilitation process of gait in people over eighteen years old with neurological damage.